Customer Relationship Management Moderation in School Selection at Al Ibrah Gresik - Triasmono Triasmono; Mu'minatus Sholichah; Eva Desembrianita (PALAPA, 2023)
This research explores the moderating influence of Customer Relationship Management (CRM) on Word of Mouth (WOM), service quality, and school location in relation to school selection decisions at AI Ibrah Gresik Integrated Islamic Middle School. The study adopts a quantitative descriptive research approach and collects data from SD IT AI Ibrah and SMP IT AI Ibrah, situated in JI. Brotonegoro Gresik, East Java, Indonesia. Smart PLS 3 software is employed for data analysis. The study reveals several significant findings. Firstly, Word of Mouth (WOM) directly impacts election decision, where recommendations and experiences from others play a vital role in individuals' decision-making process. Secondly, service quality is identified as a crucial factor influencing election decision, as individuals tend to favor schools offering high-quality services. Additionally, school location has a direct influence on election decision, with geographical factors and accessibility significantly influencing parents' school choices. Moreover, Customer Relationship Management (CRM) also holds a direct impact on election decision. Effective interactions and communications between the school and parents substantially affect the decision-making process. Furthermore, CRM is observed to moderate the relationship between WOM and election decision, as well as the link between service quality and election decision. However, CRM is found to be incapable of moderating the interaction between school location and election decision.